SCRIB Promotes Proliferation and Metastasis by Targeting Hippo/YAP Signalling in Colorectal Cancer - Hengyang Shen; Changzhi Huang; Jingyu Wu; Jie Li; Tao Hu; Zhenling Wang; Hongqiang Zhang; Yu Shao; Zan Fu (Frontiers in Cell and Developmental Biology, 2021)
The complex in which scribble planar cell polarity protein (SCRIB) is located is one of the three main polar protein complexes that play an important role in maintaining epithelial polarity and affecting tumour growth. However, the role of SCRIB in colorectal cancer (CRC) remains largely unknown. This study used date from The Cancer Genome Atlas (TCGA) and clinical samples to determine the expression of SCRIB in CRC and explored its mechanism through bioinformatics analysis and in vivo and in vitro experiments. In this study, SCRIB was found to be highly expressed in CRC patients, and it was often associated with malignant characteristics, such as proliferation, apoptosis, and epithelial-mesenchymal transition (EMT). Furthermore, we found that SCRIB may interact with the Hippo signalling pathway and affect the phosphorylation of YAP and its distribution inside and outside of the nucleus. We concluded that increased expression of SCRIB is likely to inhibit the Hippo signalling pathway by promoting YAP phosphorylation. This role of SCRIB in the progression of CRC provides an important information for the treatment of CRC.